부산 공단지역 PM-10, PM-2.5 중 유해중금속 농도분포 및 위해성 평가 - 사상공단을 중심으로 - 최성화; Seong-hwa Choi; 최성우; Seong-woo Choi; 김동영; Dong-yeong Kim; 차영욱; Young-wook Cha; 박승우; Seung-woo Park; 이서이; Seo-i Lee; et al. (환경분석과 독성보건, 2021)
We investigated the distribution of hazardous heavy metals (As, Cr6+, Ni, Cd, Pb, and Mn) and estimated the health risk related to the heavy metals in fine dust (PM-10 and PM-2.5) of Sasang industrial complex, Busan, Korea. The concentration of fine dust in the industrial complex was 1.2 times higher than in a residential area, while harmful heavy metals showed a difference of at least 1.3 times (Cd) and up to 6.5 times (Ni). The concentration of fine dust and carcinogenic heavy metals in the industrial complex increased significantly compared to the residential area in spring (March to May) and winter (December to February) months. A risk assessment was performed using Monte-Carlo simulations containing a four-step procedure. During hazard identification, As, Cr6+ Ni, Cd, and Pb were categorized as human carcinogens and probable human carcinogens and evaluated for their levels of excess cancer risk. For concentrations of over 90% Cr6+and As, the excess cancer risk was over 10-5 (1 person per 100,000). The non-cancer hazard index of As, Cr6+, Cd, and Mn was below the limit value of 1. KCI Citation Count: 0